Effect of removable partial dentures on the periodontal health of abutment and non-abutment teeth: A systematic review - S. M. Karthickraj; K. S. Dash; M. Ghadage; D. Patil; M. P. Shenoy; P. Dalave; S. Shenvi; A. Mathur (Эндодонтия Today, 2025)
AIM. Removable partial dentures (RPDs) are commonly used to restore function and aesthetics in partially edentulous patients. However, their impact on the periodontal health of abutment teeth remains a concern. This systematic review aimed to assess the periodontal outcomes associated with the use of RPDs, focusing on parameters such as probing depth (PD), gingival index (GI), plaque index (PI), and tooth mobility (TM).MATERIALS AND METHODS. A systematic search was conducted across multiple databases, including PubMed, Scopus, and Web of Science, to identify studies published from 2000 to 2024. The selection criteria included studies that evaluated periodontal health in patients using RPDs, with a minimum follow-up period of 6 months. Data extraction focused on changes in PD, GI, PI, and TM before and after RPD use. The methodological quality of the included studies was assessed using standard criteria.RESULTS. A total of n = 17 studies were included in this review, encompassing 980 patients. The majority of studies reported an increase in PD and PI in abutment teeth post-RPD insertion, with significant deterioration observed in 12 studies. GI was also noted to worsen in 10 studies, indicating increased gingival inflammation. TM increased in several studies, particularly in those with longer follow-up periods. The findings suggest that RPDs contribute to a decline in periodontal health, particularly in abutment teeth.CONCLUSIONS. The use of RPDs is associated with adverse periodontal changes in abutment teeth, including increased PD, PI, GI, and TM. These findings underscore the importance of regular periodontal maintenance and careful prosthetic design to mitigate the negative impact of RPDs on periodontal health.